2015
DOI: 10.3832/ifor1318-007
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod diversity in pure oak forests of coppice origin in northern Thrace (Turkey)

Abstract: © iForest -Biogeosciences and Forestry IntroductionTurkey is one of the world's richest countries in terms of the variety of oak species and their extent. Oak forests cover vast areas in Northern Thrace (European Part of Turkey): 656 004 ha, or 27.7% of the entire land area, of which oak forests make up 71.7% of forest lands (Makineci et al. 2011). In the past, most oak forests were managed as coppice via clear cuttings on 20-year rotations. However, the intensive use of the forest led to its long-term degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Large trees provide nesting habitat for many birds especially for resident species and cavity nesters (Jokimaki & Solonen 2011). Keten et al (2014) showed that insect diversity and abundance increased with tree DBH and tree height in coppiced Thracian oak forests. Thus, high insect abundance and diversity may be responsible for the greater bird diversity and numbers observed at tall and dense stands in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Large trees provide nesting habitat for many birds especially for resident species and cavity nesters (Jokimaki & Solonen 2011). Keten et al (2014) showed that insect diversity and abundance increased with tree DBH and tree height in coppiced Thracian oak forests. Thus, high insect abundance and diversity may be responsible for the greater bird diversity and numbers observed at tall and dense stands in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Other vegetation attributes driving arthropod taxonomic and community compositional differences between plantation types are vegetation height (Keten et al 2015), the depth and availability of leaf litter (Skarbek et al 2020) and deadwood volume (Seibold 2015). Deadwood volume was significantly higher in the mixed than in the monoculture plantation stands and probably could serve as a vital microhabitat, offering refuge from either birds or other predating arthropods and food resources essential for most arthropod groups (Parisi et al 2018;Dufour-Pelletier et al 2020;Haeler et al 2021).…”
Section: Effect Of Habitat Characteristics On Arthropod Taxonomic And...mentioning
confidence: 99%
“…petraea and east Black Sea oak-Q. pontica ) grow extensively in eastern Black Sea region of Turkey (Hedge and Yaltirik, 1982;Yaltirik, 1984;Todaro et al, 2013l;Demeter et al, 2014;Keten et al, 2015;Sen et al, 2016;Yilmaz, 2017).…”
Section: Introductionmentioning
confidence: 99%